A New Take on an Old Remedy: Generating Antibodies against Multidrug-Resistant Gram-Negative Bacteria in a Postantibiotic World - Michael P. Motley (American Society for Microbiology, 2017)
ABSTRACT With the problem of multidrug-resistant Gram-negative pathogens becoming increasingly dire, new strategies are needed to protect and treat infected patients. Though abandoned in the past, monoclonal antibody therapy against Gram-negative bacteria remains a potential solution and has potential advantages over the broad-spectrum antibiotics they were once replaced by. This Perspective reviews the prospect of utilizing monoclonal antibody therapy against these pathogens, as well as the challenges of doing so and the current therapy targets under investigation.